Biotransformation of varieties of food waste supplemented by bonemeal and eggshell powder using vermicomposting technology - Kishor Kumar Maharjan; Prakrit Noppradit; Warangkana Jutidamrongphan; Kuaanan Techato; Rabindra Prasad Dhakal (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: The quality of compost is a significant concern worldwide. This study aims to improve vermicompost quality through the utilization of enriched materials.